1999
DOI: 10.1089/clm.1999.17.155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er,Cr:YSGG Laser Irradiation in Human Enamel and Dentin: Ablation and Morphological Studies

Abstract: These results suggest that during the Er,Cr:YSGG laser irradiation, water spray directed at the ablation sites increases the ablation depths and water plays an important role as an initiator of the ablation of dental hard tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
2
32

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 13 publications
6
113
2
32
Order By: Relevance
“…Such alterations have both macro-and micro-roughness. Laser-induced changes in the surface texture of enamel and dentin could potentially affect the microleakage of adhesive restorative materials 16) . Microleakage is the main causative factor for the high incidence of secondary caries in the cervical region and accounts for many failed restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Such alterations have both macro-and micro-roughness. Laser-induced changes in the surface texture of enamel and dentin could potentially affect the microleakage of adhesive restorative materials 16) . Microleakage is the main causative factor for the high incidence of secondary caries in the cervical region and accounts for many failed restorations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Er,Cr:YSGG laser used in the current study may have effects similar to those of Er:YAG laser since its wavelength (2.78 nm) is close to that of Er:YAG laser (2.94 nm). 36 The efficacy of Er,Cr:YSGG laser for surface treatment of dentin, 37,38 ceramics 38 and composite resin 39 has been previously evaluated. Kurtulmus-Yilmaz et al evaluated the effect of Er,Cr:YSGG laser on micropush-out bond strength of fiber post to resin core, and showed that laser irradiation in 1 W and 1.5 W powers enhanced the bond strength, but 2 W laser irradiation had no such effect.…”
Section: Discussionmentioning
confidence: 99%
“…(5,6) Studies by Hossain et al, have shown that in laser-irradiated dentin surfaces the orifices of the dentinal tubules are large and irregular, and no smear layer or thermal changes such as fusion and carbonization are visible. (7) In contrast, Yamazaki et al, reported that high-power laser irradiation led to fusion, carbonization and formation of big cracks on the root canal walls. (8) In addition to post type and cleaning of the root canal, the cement type affects also post retention.…”
Section: Introductionmentioning
confidence: 98%